Achyranthes bidentata polypeptide k enhances the survival, growth and axonal regeneration of spinal cord motor neurons in vitro. Issue 6 (7th April 2021) - Cai, Ergai; Cheng, Qiong; Yu, Shu; Ding, Fei
Abstract : Achyranthes bidentata polypeptide k (ABPPk), a powerful active component from a traditional Chinese medicinal herb-Achyranthes bidentata Bl., has exhibited promising neuroprotective activity due to its multiple-targeting capability. However, the effect of ABPPk on the survival, growth and axonal regeneration of spinal cord motor neurons remains unclear. Here, a modified method, which is more optimized for embryonic cells in ambient carbon dioxide levels, was used for acquisition of rat embryonic spinal cord motor neurons with high survival and purity. ABPPk concentration-dependently enhanced the neuronal viability and promoted the neurite outgrowth. Co-culture of motor neurons and skeletal myocytes model indicated that ABPPk enhanced the neuromuscular junction development and maturation. A microfluidic axotomy model was further established for the axonal disconnection, and ABPPk significantly accelerated the axonal regeneration of motor neurons. Furthermore, we demonstrated that the upregulation of three neurofilament protein subunits in motor neurons might be relevant to the mechanisms of the growth-promoting effect of ABPPk. Our findings provide an experimental and theoretical basis for the development of ABPPk as a potential application in the development of treatment strategy for nerve injury diseases.